The Puppet Show - Schaffner, Ingrid; Kuoni, Carin; Bell, John; Gower, Terence; Osman, Jena; Pemberton, John; Taylor, Jane; Taylor, Michael R.; Weiss, Allen S.; Institute of Contemporary Art, Philadelphia (Philadelphia : Institute of Contemporary Art, 2008)
Ben-Ner, Guy ; Blake, Nayland ; Bourgeois, Louise ; Cattelan, Maurizio ; Chu, Anne ; Djurberg, Nathalie ; Gower, Terence ; Japanther ; Graham, Dan ; Huyghe, Pierre et al.
The Puppet Show, Institute of Contemporary Art, Philadelphia, January 18 - March 30, 2008
kunstcatalogus